Cross-Cultural Management: A Systematic Literature Review (SLR) - Lisan, Pasihul; Afrianti, Ulfa; Wulandari, Susi; Anshori, Mochammad Isa; Safrizal, Helmi Buyung Aulia (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
Cross-cultural management is the understanding of cultural phenomena, customs and habits that are different from or contrary to the national culture and accepting the national and accepting and adapting with an inclusive attitude. In addition, the organisational climate is invisible and invisible and untouchable. The purpose of this study is to analyse cross-cultural management in various countries. The method used in this research is the Systematic Review method using VosViewer. Data sources obtained from Google Scholar for the period 2021-2023. The results obtained from 50 journals were then subjected to data reduction with inclusion and exclusion criteria obtained 29 and 10 journals to be reviewed. The results of this study call Cross-cultural management is the process of identifying and integrating cultures Company managers can help employees practice through more professional learning.